MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATERI SIFAT-SIFAT CAHAYA MELALUI PEMBELAJARAN INKUIRI - Lestari, Siti Nur Azizah Puji Ayu; Jayadinata, Asep Kurnia; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
The students' science process skills are the problems studied in this research. The facts encountered in the field are not all teachers can develop students' science process skills and apply meaningful learning to students. One of the strategies that can be used by teachers in overcoming the problem is to apply inquiry learning model in learning. Through inquiry learning, student learning process will be more meaningful. Through inquiry, students will also be trained in their science process skills. The method used in this research is classroom action research, through the method is expected to improve students' science process skills. The research was conducted in three cycles, the result of the improvement of students science process skill in the first cycle reached 74%, the second cycle was 76%, 100% cycle III. Therefore, it can be concluded that improving the skills of science process students of grade V SDN Pasanggrahan 2 Sumedang on the material properties of light through inquiry learning is said to succeed.